Pengaruh Faktor Sosial Ekonomi Rumah Tangga terhadap Sikap Kesehatan Reproduksi pada Remaja - Wulandari, Wahidah Ayu; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 5, Mei 2017 (pp. 677 - 919), 2017)
The purpose of this study is the first to determine the influence of gender, Mother education, knowledge and income of parents of adolescent reproductive health attitudes in the district of Kuta. The data collection is done by observation, questionnaires and conducted in-depth interviews. The sampling technique using non-random sampling method in particular accidental sampling, with 174 samples. Data were analyzed by using factor analysis and multiple linear regression analysis that had previously been fitted with the classical assumption. The test results obtained results gender, Mother education, knowledge and income of parents simultaneously significant effect on the attitude of adolescent reproductive health in the district of Kuta. Partially sex, education Mother, knowledge, income parents positive and significant impact on the attitude of Adolescent Reproductive Health in Sub At Kuta (Y). The R2 in this study was 0.704, or 70.4 percent
Keywords: remaja; sosial ekonomi; sikap; kesehatan reproduksi